SISTEM PENUNJANG KEPUTUSAN UNTUK MENDETEKSI KERUSAKAN PADA SEPEDA MOTOR MANUAL MENGGUNAKAN METODE FOWARD CHAINING BERBASIS ANDROID - Rendi yashah; Mochamad Adhari Adiguna (PT Triputra Sejahtera Prima, 2023)
The rapid development of technology affects the public's need for a service that is not limited by time and space, nowadays it encourages the need for a system, methodology, strategy, and software that will help the process of detecting damage to motorbikes. However, the problem still exists in a repair, problems that often arise are usually in analyzing the damage and making repairs on motorbikes. The analysis system that is still manual is still a problem for workshop mechanics and motorcycle users.Expert systems are made with the waterfall method and by implementing the forward chaining method. Waterfall is the oldest software development method because of its natural nature. The Waterfall method is the earliest SDLC (Software Development Life Cycle) approach used for software development. The sequence in the Waterfall Method is serial which starts from the planning, analysis, design, and implementation process of the system.This system works to solve problems for motorcycle users and workshop mechanics using the JAVA programming language. The results of this application can analyze, detect and provide solutions to motorcycle damage.